2016
DOI: 10.2527/jas.2016-0275
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of collection method and diet effects on apparent digestibility and energy values of swine diets1

Abstract: Two experiments were conducted to investigate the effects of collection method and diet on estimating digestibility values. In Exp. 1, 24 barrows were fed either a cornsoybean meal diet (CSBM) or CSBM with 20% dried distillers grains with solubles (DDGS). Fecal collections were based on exact timing (Day collection) or marker-tomarker collection (MM) methods during a 4-d period. Diets contained 0.5% of titanium dioxide (TiO 2 ) for estimating digestibility using the index method. In Exp. 2, the effects of coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
(69 reference statements)
2
16
2
1
Order By: Relevance
“…The variations between 338 and 478 kcal kg -1 for DE and ME, respectively, between the methods used in the present study are close to the 261 to 678 kcal kg -1 for DE and 244 to 620 kcal kg -1 for ME observed by Gutierrez et al (2014) and Anderson et al (2012). Li et al (2016) also recorded a lower energy digestibility in diets containing DDGS as determined by the marker method in comparison with total collection.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The variations between 338 and 478 kcal kg -1 for DE and ME, respectively, between the methods used in the present study are close to the 261 to 678 kcal kg -1 for DE and 244 to 620 kcal kg -1 for ME observed by Gutierrez et al (2014) and Anderson et al (2012). Li et al (2016) also recorded a lower energy digestibility in diets containing DDGS as determined by the marker method in comparison with total collection.…”
Section: Discussionsupporting
confidence: 82%
“…As a result, fecal output increased with a reduction of DM digestibility (Widyaratne and Zijlstra, 2007). Reductions in DM digestibility as a function of an increase in DDGS in pig diets were also reported by Agyekum et al (2016), Wang et al (2016), Li et al (2016), and Wahlstrom et al (2013), who included up to 300, 200, 200, and 300 g kg After starch is removed in the ethanol production process, the organic matter present in DDGS will be closely linked to the protein, oil, and fiber fractions. Therefore, the higher NDF concentrations observed in DDGS in relation to corn end up negatively influencing the organic matter digestibility, which was observed in the current study.…”
Section: Discussionmentioning
confidence: 66%
“…Data collection for digestibility calculation was according to the method described by Li [8]. Feces were collected during the last two weeks (the 7th and 8th week) of the feeding trial.…”
Section: Methodsmentioning
confidence: 99%
“…Feces were collected during the last two weeks (the 7th and 8th week) of the feeding trial. Feed intake was timed, limited (based on daily requirement) and constantly monitored until the amount of daily intake and feces remained relatively constant (not fluctuating) during continuous 7 d at the 6th week before the collection period [8]. Feces were collected daily during 14 d. Fresh weight of daily feces was recorded and sundried until their weight constant, then 10% of collectively sundried feces were sampled and sent to laboratory for nutrient analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation